ANALISIS FRAMING PEMBERITAAN KAMPANYE PASANGAN CALON NOMOR URUT 02 PRABOWO SUBIANTO DAN SANDIAGA SALAHUDDIN UNO PADA PEMILIHAN PRESIDEN 2019 DI VIVA.CO.ID - Arif Afandy; Chelsy Yesicha (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The 2019 presidential election will be the venue for a rematch of the 2014 presidential election. President Joko Widodo once again confronts Prabowo Subianto, lieutenant of retired general and founding figure while leading the Gerindra. In this regard, the mass media, both printed or electronic, plays an active role in conveying information about the election activities. News is an result of a construction process which contains a information which is believed the truth by a media. News framing was doing by a media have an ending a receive message by audience with a purposes for give a message to audience about facts which already arranged such a way good. The purposes of this research is have to known how mass media make a reality construction in reporting Prabowo-Sandi campaign about analysis framing.The type of research used a qualitative research with an approach framing analysis. This kind of research is analysis descriptive which purposes for describe an character of news in viva.co.id things about campaign of Prabowo-Sandi. analysis data technique used framing analysis with approach of Zhongdang Pan and Gerald M.Kosicki which consist a sintaksis, script, thematic, and rhetorical.Result of this researh showing us if viva.coc.id try to build a construction of which approach by the truth of reality. Which means viva.co.id try to build social reality in our society to a step closer to the truth of reality of the truth if Prabowo and Sandiaga Uno have a type of personality which powerful, assertive, and patriotic but humble and polite. Viva.co.id have a consistent frame a tragedy about campign which does by Prabowo Subianto and Sandiaga Salahudin Uno to a better way. But this framing effort still on a reasonable ways because viva.co.id still try to keep the neutrality and objectivity on news delivering.Key words: news, reality construction, framing analysis.